Gondwanan Perspectives: Mesozoic and Cenozoic Micropaleontology of South America, Progresses and Applications - Concheyro, Graciela (2023)
This special issue Gondwana Perspectives, entitled “Mesozoic and Cenozoic Micropaleontology of South America, progresses and applications”, provides an update on several topics of micropaleontology developed by South American researchers.The issue focuses on classical micropaleontology, accurately defining relative ages and paleoenvironments, and attempts to introduce other valuable applications, such aspaleoceanographic proxies.Finally, we hope that by reading the chapters, our colleagues from abroad, unfamiliar with publications in Spanish, may have access to new relevant information on our South American sedimentary basins and may project future scientific collaborations.